Biosurfactants: The green generation of speciality chemicals and potential production using Solid-State fermentation (SSF) technology. (January 2021) - Banat, Ibrahim M.; Carboué, Quentin; Saucedo-Castañeda, Gerardo; de Jesús Cázares-Marinero, José
Graphical abstract: Highlights: Biosurfactants are becoming the specialty chemicals for many future industrial applications. Solid-state fermentation can mitigate some drawbacks of submerged liquid fermentation. Industry shows growing interest in biosurfactants for use in different markets. Covid-19 may boost future inclusion of biosurfactants in personal care products. Abstract: Surfactants are multipurpose products found in most sectors of contemporary industry. Their large-scale manufacturing has been mainly carried out using traditional chemical processes. Some of the chemical species involved in their production are considered hazardous and some industrial processes employing them categorised as "having potential negative impact on the environment". Biological surfactants have therefore been generally accepted worldwide as suitable sustainable greener alternatives. Biosurfactants exhibit the same functionalities of synthetic analogues while having the ability to synergize with other molecules improving performances; this strengthens the possibility of reaching different markets via innovative formulations. Recently, their use was suggested to help combat Covid-19. In this review, an analysis of recent bibliography is presented with descriptions, statistics, classifications, applications, advantages, and challenges; evincing the reasons why biosurfactants can be considered as the chemical specialities of the future. Finally, the uses of the solid-state fermentation as a production technology for biosurfactants is presented.